Jihad A South African Perspective - Solomon, Hussein (UJ Press, 2013)
What are the factors which have made South Africa so appealing to terrorist and radical islamic organisations? What role has South Africa played within global Jihad? This book examines how South Africa has come to play a major role in global terror networks stemming from growing criminality and corruption within state structures. It also examines the interaction between local and foreign extremist elements which undermine South Africa's security. The author brings the discussion beyond the usual mundane academic treatise to the sharp reality of the global dangers of politicised Islam - a muslim talking candidly about Islam.